Exploring Cross-Sectoral Implications of the Sustainable Development Goals: Towards a Framework for Integrating Health Equity Perspectives With the Land-Water-Energy Nexus - Christiana O. Onabola; Nathan Andrews; Maya K. Gislason; Henry G. Harder; Margot W. Parkes (Frontiers Media S.A., 2022)
Objectives: To assess existing evidence and identify gaps in the integrative framework of the Sustainable Development Goals (SDGs) for their potential to advance cross-sectoral perspectives and actions that connect health equity with the land-water-energy nexus in a watershed context.Methods: Five bibliographic databases were searched from 2016 to 2021. This yielded an initial 226 publications, which were screened for titles, abstracts, and full texts on DistillerSR; resulting in a final 30 publications that were studied. These keywords defined the search terms: "health equity," "SDGs," "watershed," "resource nexus," and "cross-sectoral."Results: Thematic syntheses of debates and gaps point to the relevance of the SDGs as a cross-sectoral, integrative platform for place-based programming of the land-water-energy nexus, and to account for negative externalities and cascaded impacts on human and environmental health.Conclusion: For the purpose of monitoring health equity in the contexts of interactions of land, water, and energy in rural, remote, and Indigenous contexts, and on the basis of the SDGs, this paper generates evidence to inform health equity-oriented policies, programs and practices, and to enhance health for equity-seeking populations.